Teachers’ professional identities: Narratives of KSSR English language teachers in Malaysia - Halim, H.A. (2016)
Educational reforms have swept across the globalized world, and in the field of English language teaching (ELT), there is no exception. The Malaysian Education Blueprint 2013-2025 has featured the country’s ambitious yet achievable and feasible tasks to build a strong and efficient education system by 2025 that aims to ensure every child is proficient in Bahasa Malaysia and English language. In doing that, a key priority for this transformation is to first ensure better alignment between policy formulation and implementation along the entire education value chain (MOE, 2012). Another priority is to improve resource productivity by strengthening the link between desired outcomes and the effective allocation of resources as well as efficient implementation and evaluation of relevant programmes and projects (MOE, 2012). For the aforementioned reasons, the English Language Curriculum for Primary School has been introduced and implemented in primary schools in Malaysia starting 2011. This policy is commonly known by its Bahasa Malaysia acronym, KSSR. The Curriculum Development Division (CDD, 2011) stated that the new curriculum aims to overcome illiteracy problems among primary school students and to improve quality of teaching and learning process. There are six pedagogical principles outlined in this curriculum: back to basics, learning is fun, meaningful and purposeful learning, teaching is learner-centred, integration of salient new technologies, assessment for learning and character-building infused (CDD, 2011). The implementation of these six pedagogical principles is hoped to enhance language acquisition of students in English, improve quality of teaching and learning as well as to overcome the problem of illiteracy among primary school students in Malaysia. Evidently, Malaysia is one of the countries where English is taught as a second or foreign language that have witnessed the introduction of many western-rooted methodologies such as Communicative Language Teaching and Task-based Learning. Emphasizing the role of interaction in language learning, these language pedagogies view this process as a social practice in real situations (Nunan, 2004). In Malaysia, these language pedagogies have been warmly welcomed by the educational administration and promulgated as part of the curriculum requirements. In actual classroom practice, however, these reforms might have been met with resistance from teachers who remain attached to traditional pedagogies featuring teacher-centred, test-oriented and rote-based teaching and learning (Tsui, 2007). The competing demands of the old and new systems thus create a unique workplace environment for pedagogical adaptation and renegotiation of teachers’ professional identities.